Rancang Bangun Game Dreamcatcher : War Of Surabaya Dengan Permodelan Scrum - ferdianza, boby (INTEGER: Journal of Information Technology, 2018)
History belongs to a compulsory element in the teaching and learning at school. It can help students to know and more appreciate the past events. The number of history materials taught at school sometimes causes difficulty for students to learn. The lack of facilities and learning media which can attract student’s interest becomes the main factors of student’s difficulty in learning Social Science. Learning medium is very vital to determine what materials students can learn. One of solutions to solve difficulty in learning history is by creating new learning medium in the form of educational game as it can arouse student’s ability in thinking. One of the games teaching history particularly the history of Surabaya is Dreamcatcher: War of Surabaya. This game was designed based on historical events in Surabaya composed in an attractive story. It is completed with quiz to improve student’s memory. Game “Dreamcatcher: War of Surabaya” can be played with android platform and it is considered successful in teaching the history of Surabaya as it could improve students’ abilities on Surabaya history by 113.7% based on the results of pre-and post-tests.